Inclusive Education for Children With Disabilities - Santoso, Harri; Nurafni, Nurafni; Rahmi, Nuzulul (JOURNAL OF EDUCATION SCIENCE, 2015)
This article discuss about inclusive education concept for children with disabilities. Based on Law No. 4 Â 1997 on persons with disabilities, Â This term used to the person who has a mental or physical difficulties and disorder, which may interfere with or be seen as a barrier and a barrier in performing normal activities such as deaf, blind and learning disabilities. Inclusive education is the provision of education system that provides opportunities for all learners who has the disorder and intelligence or special talent to participate in general education (PerMendikNas No. 70 2009). This study attempt to explain inclusive education for the children with disabilities referring to the results previous research. Good understanding in inclusive education is able to educate the children with disabilites effectively.